Detection of Psychobiological, Environmental, and Behavioral Risk Factors on Hypertension Prevention Efforts in Agro-Industrial Communities - Alestya Putri Jathy; Febri Endra Budi Setyawan; Indra Wahyu Saputra (International Medical Journal Corp. Ltd, 2025)
Background : Hypertension is one of the leading non-communicable diseases that contributes significantly to global mortality and imposes a major economic and public health burden, including in Indonesia. The agro-industrial community has a high level of vulnerability to hypertension due to the complex interplay of psychobiological, environmental, and behavioral risk factors. Effective hypertension prevention strategies need to consider these factors to ensure that interventions are well-targeted and sustainable. Objective : To determine the influence of psychobiological, environmental, and behavioral risk factors on hypertension prevention efforts among the agro-industrial community in Trenggalek Regency. Methods: This study employed an analytical observational design with a cross-sectional approach. A total of 348 respondents, representing the agro-industrial community, were selected using a systematic random sampling technique. Data were collected using a structured questionnaire that had been tested for validity and reliability. Data analysis was performed using the Structural Equation Modeling–Partial Least Squares (SEM–PLS) method. Results: : The results showed that the three main factors—psychobiological (age, sex, and genetics), environmental (stress and social well-being), and behavioral (dietary habits, smoking, and physical activity)—significantly influenced hypertension prevention efforts. Primary and secondary prevention had a greater impact on reducing hypertension risk compared to tertiary prevention. Age, educational level, and smoking habits were the most dominant factors affecting hypertension prevention. Conclusion: The study concludes that psychobiological, environmental, and behavioral factors significantly affect hypertension prevention efforts among the agro-industrial community.